The human trafficking debate: Implications for Social Work Practice - Soma Sen; Yoko Baba (Social Work & Society, 2017)
The present paper examines the claims making process and the varied constructions of human trafficking as a social problem. We have utilized the theoretical framework of Social Constructionism to answer questions: (1) What is the process utilized in social problems constructions in general? (2) How is this process applied to elucidate the current debate on the social problem of human trafficking, in particular? We have also suggested using a critical framework when intervening with human trafficking and delineated some practice implications for social service providers.